Jasmonic acid application triggers detoxification of lead (Pb) toxicity in tomato through the modifications of secondary metabolites and gene expression. (November 2019) - Bali, Shagun; Jamwal, Vijay Lakshmi; Kohli, Sukhmeen Kaur; Kaur, Parminder; Tejpal, Ruchi; Bhalla, Vandana; Ohri, Puja; Gandhi, Sumit G.; Bhardwaj, Renu; Al-Huqail, Asma A.; Siddiqui, Manzer H.; Ali, Hayssam M.; et al.
Abstract: Jasmonic acid (JA) is an important phytohormone associated in defense responses against stress. Crop plants experience heavy metal toxicity and needs to be explored to enhance the crop production. Lead (Pb) is one of the dangerous heavy metal that pollutes soil and water bodies and is released from various sources like discharge from batteries, automobile exhaust, and paints. The present study was designed to evaluate the role of JA (100 nM) on photosynthetic pigments, secondary metabolites, organic acids, and metal ligation compounds in tomato seedlings under different concentrations of Pb (0.25, 0.50, and 0.75 mM). It was observed that Pb treatment declined pigment content, relative water content, and heavy metal tolerance index. Expression of chlorophyllase was also enhanced in Pb-treated seedlings. Seeds primed with JA lowered the expression of chlorophyllase under Pb stress. JA application enhanced the contents of secondary metabolites (total phenols, polyphenols, flavonoids, and anthocyanin) which were confirmed with enhanced expression of chalcone synthase and phenylalanine ammonia lyase in Pb-exposed seedlings. Treatment of JA further elevated the levels of organic acids and metal chelating compounds under Pb toxicity. JA up-regulated the expression of succinate dehydrogenase and fumarate hydratase in Pb-exposed seedlings. Results revealed that seeds primed with JA reduced Pb toxicity by elevating, the levels of photosynthetic pigments, secondary metabolites, osmolytes, metal ligation compounds, organic acids, and polyamine accumulation in tomato seedlings. Highlights: JA application improved chlorophyll content by reducing the expression of chlorophyllase in Pb-stressed tomato seedlings. JA treatment elevated the expression of chalcone synthase and phenylalanine ammonia lyase under Pb stress. JA application upregulated the expression of succinate dehydrogenase and fumarate hydratase in Pb-treated seedlings. JA treatment enhanced in vitro polyamine accumulation under Pb stress.